2021
DOI: 10.1016/j.bjps.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical training during the COVID-19 pandemic: Challenges and opportunities for junior trainees

Abstract: The practice of partial mastectomy (PM) in patients with breast cancer has gained momentum over total mastectomy since the results of randomized clinical trials that have provided evidence demonstrating equivalent survival. 1 But in recent years there has been a relative decline in PM compared to bilateral mastectomies, which has been attributed to inadequate esthetic outcomes after PM without reconstruction, which ultimately affects patient satisfaction and their health-related quality of life. 2 On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…73.2% of our respondents reported shortening of patients’ stay or changing the type of anesthesia from general to local (40.8%) in the departments, which may be dictated by minimizing the risk of contamination. 4 Testing patients before the admission protects the healthcare workers from COVID-19 exposure and decreases the risk of interpatient transmission. The majority of our respondents indicated that either a PCR test or an antigen test was required before admission (80.3%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…73.2% of our respondents reported shortening of patients’ stay or changing the type of anesthesia from general to local (40.8%) in the departments, which may be dictated by minimizing the risk of contamination. 4 Testing patients before the admission protects the healthcare workers from COVID-19 exposure and decreases the risk of interpatient transmission. The majority of our respondents indicated that either a PCR test or an antigen test was required before admission (80.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The following timeframes were taken first wave - 23.01.2020 to 31.05.2020, the interim period - 01.06.2020 to 30.09.2020, the second wave - 01.10.2020 to 28.02.2021. 15 , 16 Visualization was prepared in GraphPad PRISM 9.1, (CA, USA) and Datawrapper (Berlin, Germany). Data on COVID-19 cases number were acquired/retrieved from https://ourworldindata.org/coronavirus.16 Fisher's exact test, and R-spearman correlation were used to analyze the data (GraphPad PRISM 9.1, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This period also brought with it a lack of access to surgical facilities including a limited supply of PPE, decrease in the workforce and a reduced number of skilled anesthetists, all in all contributing to the lack of proper surgical training. 12 The United States, United Kingdom, Canada and New Zealand saw nationwide postponement of surgical board exams and in-training assessment activities were heavily modified. 13 None of these developed countries were successful in implementing proper national guidelines for surgical trainees to operate during the COVID-19 era.…”
Section: Discussionmentioning
confidence: 99%
“…The increased use of online didactics and additional time also resulted in additional opportunities for professional and personal development for trainees [33]. We have personally noticed an overall increased time window for literature review and background reading, work on clinical research projects, and manuscript writing time.…”
Section: Unforeseen Opportunitiesmentioning
confidence: 99%